Spiral Computed Tomography for the Diagnosis of Appendicitis in Pregnancy - Orhan, Ayfer; Kiliç, Gökhan; Kurzel, Richard; Gürateş, Bilgin; Garon, Jack (My University, 2003)
OBJECTIVE: To survey the positive findings and determine the efficacy of spiral Computed Tomography for diagnosing appendicitis in pregnancy. STUDY DESIGN: A 5-year retrospective review yielded 99 cases of confirmed appendicitis in women of reproductive age by surgical pathology report. Of these, 13 patients (12%) were pregnant, five of whom had spiral Computed Tomography's performed Radiographic findings were reviewed, and the efficacy of spiral Computed Tomography in making the correct diagnosis determined. RESULT(s): Positive findings on spiral Computed Tomography were correctly identified in three of five cases (% 60). CONCLUSIONS: Spiral Computed Tomography is an effective technique in identifying pregnant patients with appendicitis while using low radiation exposure (0.3 rad).
Gebelikte Apandisit Tanisinda Bilgisayarli Sipiral Tomografinin Yeri
Keywords: Acute Appendicitis; Pregnancy; Spiral Computed Tomography